SOCIETY 5.0: OPPORTUNITIES AND CAREER PREPARATION OF STUDENT VOCATIONAL HIGH SCHOOL - Ihsan, Fatihul (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
Society 5.0 causes a transformation in the world of work that brings changes to the way a person works, methods, tasks, and qualifications. These conditions cause the need for workforce skills and competencies to continue to change. This research aims to determine vocational opportunities in the Era of Society 5.0 and strategies for preparing students' careers at Vocational High Schools (VHS). The research uses the SLR (Systematic Literature Review) method with literature sources taken from the Google Scholar and Scopus databases in the 2018-2023 publication period. The results of this research are a study of career problems for vocational school students, identification of current vocational opportunities, and strategies for preparing careers for vocational school students. This paper can help contribute to VHS and related institutions to solve the problem of absorption in the world of work for vocational school graduates.